2008
DOI: 10.1111/j.1540-8159.2008.01157.x
|View full text |Cite
|
Sign up to set email alerts
|

Upper Turnover Portion of the Reentry Circuit for Typical and Reverse Typical Atrial Flutter

Abstract: PMRA forms a functional block line during both typical and reverse typical AFL. The upper turnover portion of reentry circuit for AFL was observed between the upper limit of the PMRA and the posterior SVC in the majority of isthmus-dependent AFL patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Fukuzawa et al [4], however, reported that the transverse conduction in the posterior RA is not complete and that the wavefront turns around at the posterior RA below the SVC in the majority of AFL patients, based on the CARTO mapping system. Dixit et al [18] reported the evidence of posterior RA participation in the AFL circuit in about half the subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Fukuzawa et al [4], however, reported that the transverse conduction in the posterior RA is not complete and that the wavefront turns around at the posterior RA below the SVC in the majority of AFL patients, based on the CARTO mapping system. Dixit et al [18] reported the evidence of posterior RA participation in the AFL circuit in about half the subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the upper turnover site of the reentry circuit of typical AFL is anterior to the orifice of the SVC. 15,16 Fukuzawa et al, 17 however, observed the upper turnover portion of the reentry circuit in AFL at the posterior SVC in a majority of AFL patients using a CARTO mapping system. Findings of some other previous studies support this notion.…”
Section: Posterior Block Line Length During Aflmentioning
confidence: 99%
“…The reentry circuit of AFL is thought to be solely bound around the TA . Indeed, varieties of reentry circuits have been demonstrated by three‐dimensional (3D) and/or entrainment mapping . Other than at the CTI, the reentry circuit might not be fixed and not always bound around the TA.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous studies from our laboratory and others, we hypothesized that the posterior block line was located along the PMRA posterior to the CT, and the anterior part of the reentry circuit was not bound around the TA, but the CT acts as the anterior (craniocaudal) pathway of the reentry circuit.…”
Section: Introductionmentioning
confidence: 99%